2013
DOI: 10.1590/s1984-29612013005000018
|View full text |Cite
|
Sign up to set email alerts
|

Natural infection by endoparasites among free-living wild animals

Abstract: The objective of this study was to investigate the frequency of occurrence and variety of intestinal parasites among free-living wild animals. Fecal samples from wild mammals and birds at rehabilitation centers in the states of Mato Grosso do Sul and São Paulo were analyzed by sedimentation and flotation-centrifugation methods. Parasite eggs, oocysts, cysts and/or trophozoites were found in 71% of the samples. Cryptosporidium sp. oocysts were detected in fecal samples from oncillas (Leopardus tigrinus) and sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 27 publications
2
20
1
2
Order By: Relevance
“…When we analyzed feces of parrots, we found a positivity of 50%, similar to Holsback et al (2013) results, who also found Cryptosporidium spp. in samples of maritaca's feces in the State of Mato Grosso do Sul and São Paulo.…”
Section: Panthera Oncasupporting
confidence: 89%
See 1 more Smart Citation
“…When we analyzed feces of parrots, we found a positivity of 50%, similar to Holsback et al (2013) results, who also found Cryptosporidium spp. in samples of maritaca's feces in the State of Mato Grosso do Sul and São Paulo.…”
Section: Panthera Oncasupporting
confidence: 89%
“…Holsback et al (2013) also found the protozoa in the same animal species in Mato Grosso do Sul and Southern Sao Paulo region.…”
Section: Panthera Oncamentioning
confidence: 64%
“…In addition, the contrary effect, related to the transfer of parasitic infections from wild animals to domestic dogs, may occur, and in this case, the prevalence of dog parasites represent a bio-indicator of environmental contamination. Wild canids and felids, such as crab-eating fox (Cerdocyon thous), pumas (Puma concolor) and jaguars (Panthera onca), are present inside and surround the MDSP and are also hosts of these parasites founded in domestic dogs, such as Toxocara spp., Capillaria spp., Trichuris spp., Cystoisospora and Giardia spp., (FARRET et al, 2008;HOLSBACK et al, 2013;LIMA, 2009;SANTOS et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…No Brasil, a investigação do Cryptosporidium spp. na classe das aves tem sido conduzido por vários autores (Cardozo et al, 2005;Huber et al, 2007;Oliveira et al, 2008;Gomes et al, 2009;Nakamura et al, 2009;Silva et al, 2010;Sevá et al, 2011;Holsback et al, 2013;Nakamura et al, 2014;Cunha et al, 2016), porém nenhum estudo até o momento utilizou o hospedeiro pombo.…”
Section: Resultsunclassified